Results of Occupational Group Promotion in Krachaeng Subdistrict, Phra Nakhon Si Ayutthaya - Nuiplot, Nalin-on (Fa Nuea Journal, 2025)
The objectives of this research were: 1) Carry out activities to develop and promote the career group of chili paste product in Krachaeng Subdistrict, Bang Sai District, Phra Nakhon Si Ayutthaya Province, and 2) Evaluate the gross village happiness (GVH) of the sample group from the occupational group promotion in Krachaeng Subdistrict, Bang Sai District, Phra Nakhon Si Ayutthaya Province. The sample group consisted of 20 households, totaling 30 people, in the “Krachaeng Development Farmer Group” in Krachaeng Subdistrict, Bang Sai District, Phra Nakhon Si Ayutthaya Province. The tools used in this research were an interview form and a 5-level rating scale questionnaire. The statistics used for data analysis were SROI, percentage, and average. The results showed that: 1) Received 2 chili paste products: pork crackling chili paste and herbal crispy chicken skin chili paste. The SROI was calculated as 4.23. The results showed that this social project had created benefits that were higher than the costs incurred, and 2) The percentage of GVH of the household was 84.01 percent. The result showed that household member who participated in this project had confidence and trust in their ability to manage life factors to reduce anxiety about situations that had occurred or may occur. It then made them feel the most satisfied, comfortable, and persistent.